Indirect Speech Act in Judy Christenberry's Novel the Cowboy's Secret Son: A Pragmatic Analysis - Muntiningsih, Ratna (Universitas Swadaya Gunung Jati, 2013)
This paper presents the core of a descriptive theory of Indirect Speech acts, i.e. utterances used by the speaker to the hearer based on the three types of felicity conditions such as content condition, preparatory condition, and sincerity condition. The data examples takes from the English novel